2020
DOI: 10.1136/bmjopen-2019-035633
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of drug trial funding sources and author financial conflicts of interest in Cochrane and non-Cochrane meta-analyses: a cross-sectional study

Abstract: ObjectiveTo (1) investigate the extent to which recently published meta-analyses report trial funding, author–industry financial ties and author–industry employment from included randomised controlled trials (RCTs), comparing Cochrane and non-Cochrane meta-analyses; (2) examine characteristics of meta-analyses independently associated with reporting funding sources of included RCTs; and (3) compare reporting among recently published Cochrane meta-analyses to Cochrane reviews published in 2010.DesignReview of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In our sample, only 8/44 (18%) SR reported information on con ict of interest of the included primary studies. This is similar to an investigation of non-Cochrane reviews in which 15% of SR had reports on funding for the included primary studies [24]. Con ict of interest among authors of primary studies may also be associated with tactical choices on control groups or comparative interventions [25].…”
Section: Discussionsupporting
confidence: 60%
“…In our sample, only 8/44 (18%) SR reported information on con ict of interest of the included primary studies. This is similar to an investigation of non-Cochrane reviews in which 15% of SR had reports on funding for the included primary studies [24]. Con ict of interest among authors of primary studies may also be associated with tactical choices on control groups or comparative interventions [25].…”
Section: Discussionsupporting
confidence: 60%
“…However, the results of this study showed that in only 54.17% of MAs the FCOIs of the included primary studies were reported and listed in detail, whereas in only 21.88% of MAs, author-industry-related financial ties of included trials were reported. In a recent study, it was demonstrated that the reporting of non-Cochrane SRs and MAs on the financial relationship of the author-industry was only 1%, 39 which is far from acceptable.…”
Section: Discussionmentioning
confidence: 98%
“…A troublesome finding of this study, in our opinion, was the low frequency of SRs that presented data on financial conflict of interest among the included primary (8/44; 18%). However, according to a recent study on 250 meta-analyses, author-industry financial ties of the included trials were reported in only 1% of non-Cochrane and 44% of Cochrane meta-analyses [ 20 ]. Conflict of interest among the authors of primary studies may be associated with, e.g., tactical choices on control groups or comparative interventions [ 21 ], and we understand that information on competing interests related to the included primary studies is essential to all the end-users of SRs.…”
Section: Discussionmentioning
confidence: 99%